Sub-per-mille bunch energy spread in a quasi-linear laser-wakefield accelerator via periodical de-chirpings - Changhai Yu; Zhiyong Qin; Zhongtao Xiang; Ya Huang; Jiansheng Liu (Communications Physics)
Abstract Plasma-wakefield-based acceleration technology has enabled the generation of very bright particle bunches of ultrashort duration, micrometer size and low emittance. However, it is still extremely challenging to break through the barrier of per-mille energy spread. Here, we utilize a quasi-linear laser-driven wakefield accelerator with a uniquely designed density-modulated plasmas to achieve periodical de-chirpings of the seeded bunch and have almost eliminated the accumulated energy chirp in each period during the periodical quasi-phase-stable acceleration. Quasi-three-dimensional particle-in-cell simulations verify that a quasi-linear plasma wave with a stable propagation of more than 30-fold Rayleigh lengths can be generated to stably accelerate both the electron and positron bunches up to GeV scale. The energy spread of the bunch can be ultimately reduced to be less than 0.05% while maintaining a small beam emittance. This scheme is highly feasible and desirable for achieving an ultralow-energy-spread plasma-based accelerator and facilitating broader applications.